La planificación de auditoria basada en riesgos aplicada a la cuenta gastos de personal y su influencia en resultados - Armijos Armijos, Danessa Tamara (2015)
This work mentions the importance of audit planning based on risk, as dynamic axis for control of the accounts that are handled in the company CREATICORP SA, specifically in the bill that deals with staff costs, objectives to be achieved with this research are basically making the implementation of the audit on the account mentioned above establish whether it has made such interventions in the company and finally set the parameters that may justify the development of an integrated proposal. The study was a methodological approach correlational exploratory, since the data of the variables affecting bilaterally flujodiagramación technique was also applied to establish in the proposed questionnaires to be applied, the problem to be solved was precisely transparency administrative, operational and financial operations. After he performed the study and established the proposal with the respective phases was concluded that the company has not been audited in relation to the account personnel costs, which also have been conducted internal audits but without deep knowledge of detection of risks, and that the staff is not trained to carry out this activity, so it came to recommending that policy implementation audit planning are established, a thorough control and risk detection is necessary training on specific audit and risk detection. It is expected to contribute positively influence to be an early work of many more in various areas of accounting department, and to give as a result an increase in profitability that allows economic growth but also the business in managing its financial management.